Exhibits from the Life of Bodies - Scott, Cam (Academic Quarter | Akademisk kvarter, 2012)
The article discusses the aesthetic practice and the philosophical implications of exhibition of human remains, so-called body exhibitions. The article discusses many cases of this practice from Medieval Dances of Death to present-day zombie-lore.